2015
DOI: 10.1177/1040638715587548
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between available serologic tests for detecting antibodies against Anaplasma phagocytophilum and Borrelia burgdorferi in horses in Canada

Abstract: Abstract. To investigate the agreement between available serologic tests for the detection of antibodies against Anaplasma phagocytophilum and Borrelia burgdorferi, 50 serum samples from horses of unknown clinical status and at low risk for infection were tested. In addition to a point-of-care enzyme-linked immunosorbent assay (pocELISA), the evaluated tests included 2 indirect fluorescent antibody tests (IFATs) for antibodies against A. phagocytophilum and an IFAT, an ELISA confirmed with Western blot, and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
1
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 15 publications
0
3
1
1
Order By: Relevance
“…It would be expected that agreement between C6 ELISA and OspF would be highest as high correlations between antibodies to OspF and C6 have been shown in dogs and horses 23,26 . The results from this study show a low level of agreement between the two tests (kappa = 0.27) which is inconsistent with literature on these testing methods in endemic regions in United States but is more consistent with research from Canada in low prevalence regions 26,27 . Discordant testing complicates diagnosis of Lyme disease even further and highlights the need for additional research in this area to help clinicians make evidence‐based decisions on testing.…”
Section: Discussioncontrasting
confidence: 73%
“…It would be expected that agreement between C6 ELISA and OspF would be highest as high correlations between antibodies to OspF and C6 have been shown in dogs and horses 23,26 . The results from this study show a low level of agreement between the two tests (kappa = 0.27) which is inconsistent with literature on these testing methods in endemic regions in United States but is more consistent with research from Canada in low prevalence regions 26,27 . Discordant testing complicates diagnosis of Lyme disease even further and highlights the need for additional research in this area to help clinicians make evidence‐based decisions on testing.…”
Section: Discussioncontrasting
confidence: 73%
“…29,63 Whole cell lysate assays such as IFAT and ELISA do not distinguish between infection stages or between natural infection and vaccination. Additionally, evidence from dogs and horses suggests that whole cell lysate assays can give false positive results attributable to crossreactivity with antibodies against common bacterial antigens such as flagellar proteins, [67][68][69] and positive IFAT or ELISA results therefore require confirmation of infection by WB. Serologic surveys have demonstrated that clinically normal horses living in endemic areas often have detectable antibody levels against B. burgdorferi.…”
Section: Diagnosis Of Infectionmentioning
confidence: 99%
“…Die etwas geringere Sensitivität, die Veronesi und Mitarbeiter gefunden hatten, war vor allem durch Fälle mit niedrigen IFAT-Titern in einer Gruppe von Pferden ohne klinische Veränderungen begründet (Veronesi et al 2014). Schvartz und Mitarbeiter beurteilten die Übereinstimmung der IFAT-und ELISA-Ergebnisse in ihrer Studie an 50 Pferden einer Population mit geringem Ap-Infektionsrisiko als mäßig (Schvartz et al 2015a).…”
Section: Diagnostik Der Anaplasmoseunclassified